Uji Ketahanan Beberapa Varietas Kedelai (Glycine max (L). Merrill) terhadap Keadaan Kekeringan - Patty, Jacob Richard; Jambormias, Edizon; Ririhena, Rhony Einstein; Leiwakabessy, Christoffol; Hitijahubessy, Fabians. J.D. (JURNAL PERTANIAN KEPULAUAN, 2025)
The drought phenomenon is interlaced with something like the deviation of the pouring down. A kind plant is level property survival to be different toward drought, wear in modification by habitat zone, and physiological factors. The aims of this study are to know the stamina of the same variety of soybean toward squeezing drought in the teaching of growth diversity and plant products. The research used a split-plot design. Separated compartments with there really the trial two-factor is between them. Firstly, factor variety (V) is well-equipped, and the factor in this research analysis is the Anova test and continuing with the contrast orthogonal test. The result of this research to meet there is predispose entity drought deceleration growth and the evolution of this Soybean. The local variety of Namlea and Pasahari the survival at entity the rain is upon 90 mm at generative phase. Superior Orba variety and introduction in showed the survival toward is drought at vegetative period.